Renal Endometriosis Mimicking Cystic Renal Tumor: Case Report and Literature Review - Yang, Ye; Zhao, Xinxin; Huang, Ying (Frontiers in Medicine, 2021)
Background: Endometriosis mainly affects female pelvic tissues and organs, and the presence of endometriosis in the kidney is extremely rare. Case presentation: We report a case of a 48-year-old woman who presented with intermittent hematuria. She was found to have a cystic mass on renal ultrasonography, and contrast-enhanced computed tomography (CT) showed slight enhancement of the cystic wall and septa. These findings were indicative of cystic renal carcinoma. The patient subsequently underwent partial right nephrectomy. Histopathology revealed endometriosis of the right renal parenchyma. The patient recovered well and had no evidence of a recurrent renal mass at the 3 months’ follow up. Conclusion: The possibility of renal endometriosis should be considered in a female patient with a cystic renal mass and clinical symptoms related to the menstrual cycle.